ELECTRONIC MEDICAL RECORD DATA PROTECTION IN DIGITAL HEALTH SERVICES - Helviana Hasibuan; Rahmayanti; Poltak Marusaha Tambunan (Journal of International Islamic Law, Human Right and Public Policy, 2026)
Digital transformation in the healthcare sector is driving the adoption of electronic medical records as an effort to improve efficiency, service quality, and patient data integration. However, this digitalization also poses risks to the protection of sensitive patient personal data, such as potential data leaks, information misuse, and privacy violations. This study aims to analyze the legal protection provisions for electronic medical records and assess the effectiveness of law enforcement in digital healthcare services in Indonesia. The research method used is normative juridical with a statutory and conceptual approach. The legal materials consist of laws and regulations, scientific literature, and previous research results, which are analyzed qualitatively using descriptive-prescriptive methods. The research results show that, normatively, the protection of electronic medical records is regulated through the Personal Data Protection Law and sectoral regulations in the health sector, which emphasize the principles of confidentiality, security, and accountability of patient data. However, regulatory harmonization remains problematic, particularly regarding the division of legal responsibilities and cross-system data management mechanisms. Furthermore, the effectiveness of law enforcement remains suboptimal due to weak oversight, limited institutional capacity, low legal awareness, and uneven distribution of technological infrastructure. In conclusion, the protection of electronic medical records requires strengthening through regulatory harmonization, increased law enforcement capacity, and enhanced security systems and digital literacy. These efforts are crucial to ensure the protection of patient privacy rights while supporting the development of secure and reliable digital healthcare services.